1999
DOI: 10.1111/j.1572-0241.1999.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of in Vitro Nitroimidazole Resistance on The Efficacy of Nitroimidazole-Containing Anti- Helicobacter Pylori Regimens: A Meta-Analysis

Abstract: NIR decreases treatment efficacy. Treatment duration and choice of other drugs influence the impact of NIR on treatment efficacy. If NIR is present, a nitroimidazole-containing regimen should be avoided or a quadruple regimen should be given for > 1 wk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 71 publications
2
12
1
1
Order By: Relevance
“…This finding is in contrast with results from previous studies demonstrating the negative effect of different levels of metronidazole resistance on PPI‐based triple therapy 11, 13, 16, 17 . Moayyedi et al .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast with results from previous studies demonstrating the negative effect of different levels of metronidazole resistance on PPI‐based triple therapy 11, 13, 16, 17 . Moayyedi et al .…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have established that primary resistance to clarithromycin in H. pylori is a strong predictive factor for therapeutic failure in clarithromycin containing regimens 10–13 . On the contrary, conflicting results have been reported on the impact of primary metronidazole resistance on treatment outcome, especially in treatment combinations containing both nitroimidazole and clarithromycin 11, 13–17 . Prevalence of primary clarithromycin resistance in H. pylori is still relatively low at 3–13% in both industrialized and developing countries 11, 15, 18–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Metronidazole resistance also plays a role because resistance was shown to reduce eradication rates of clarithromycin triple therapy by 18% . Still, several studies have suggested adequate (76–82%) eradication rates among metronidazole‐resistant compared with metronidazole‐susceptible strains (), which may be a function of the ability to overcome metronidazole resistance with more frequent dosing, longer durations of therapy, and concomitant therapy with a PPI or bismuth …”
Section: Penicillin Allergymentioning
confidence: 99%
“…The bacterial cells then entered vacuoles and remained viable for at least 48 h. However, replication of the internalized H. pylori cells was not observed in the study, perhaps because of the short monitoring time and because the intracellular milieu was not suitable for bacterial replication (Amieva et al, 2002). Nonetheless, a most recent study found that H. pylori could proliferate in cells: two cells lines (AGS and MKN45) were evaluated in gentamicin protection experiments, revealing that H. pylori could proliferate after entering the cells, with the maximum number of bacterial cells observed after 6–12 h (van der Wouden et al, 1999; Rokkas et al, 2009; Chu et al, 2010). Zhang et al (2015) also observed this phenomenon in their study, whereby H. pylori attached to the cell membrane and combined with cellular microvilli after 2.5 h of infection.…”
Section: Cellular Invasion Of H Pylorimentioning
confidence: 99%